Dreaming, waking conscious experience, and the resting brain: report of subjective experience as a tool in the cognitive neurosciences - Wamsley, Erin J. (Frontiers in Psychology, 2013)
Even when we are ostensibly doing “nothing” – as during states of rest, sleep, and reverie – the brain continues to process information. In resting wakefulness, the mind generates thoughts, plans for the future, and imagines fictitious scenarios. In sleep, when the demands of sensory input are reduced, our experience turns to the thoughts and images we call “dreaming”. Far from being a meaningless distraction, the content of these subjective experiences provides an important and unique source of information about the activities of the resting mind and brain. In both wakefulness and sleep, spontaneous experience combines recent and remote memory fragments into novel scenarios. These conscious experiences may reflect the consolidation of recent memory into long-term storage, an adaptive process that functions to extract general knowledge about the world and adaptively respond to future events. Recent examples from psychology and neuroscience demonstrate that the use of subjective report can provide clues to the function(s) of rest and sleep.